Unraveling site-specific seed formation abnormalities in Picea neoveitchii Mast. trees via widely metabolomic and transcriptomic analysis - Li, Kaiyuan; Lin, Jiayi; Fan, Rong; Chen, Sibo; Ma, Zhilin; Ji, Wenli (Frontiers in Plant Science, 2024)
Picea neoveitchii Mast. is a rare and threatened species of evergreen coniferous tree in China, commonly facing issues such as damaged seeds, abnormal seed growth, and empty seed shells.These abnormalities vary by location; unfortunately, the reasons behind these inconsistencies are completely unknown. This study compared seeds from two 150-year-old trees located in Taibai (Shaanxi province, TB150) and Zhouqu (Gansu province, ZQ150). The results showed significant differences in 43 metabolites and hormone levels, with higher levels of indole-3-acetic acid (IAA), methyl jasmonate (MeJA), and brassinosteroid (BR) in ZQ150, which were associated with more viable seeds. In contrast, TB150 exhibited more damaged seeds and empty seed shells due to higher abscisic acid (ABA) levels. Moreover, to further investigate these inconsistencies, we performed de novo transcriptomic assembly and functional annotation of unigenes using highthroughput sequencing. A total of 2355 differentially expressed unigenes were identified between TB150 and ZQ150, with 1280 upregulated and 1075 downregulated. Hormone signaling and sugar metabolism-related unigenes were further examined for their role in seed development. ZQ150 increased the number of normal seeds by enhancing endogenous IAA levels and upregulating auxin signaling and sugar metabolism related genes. Conversely, TB150 showed more empty seed shells, corelated with elevated ABA levels and the activation of ABA signaling genes. We hypothesize that enhanced IAA levels and the upregulation of sugar metabolism and auxin signaling genes promote normal seed development.